HUBUNGAN ANTARA GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL DENGAN KOMITMEN TERHADAP ORGANISASI = The Relationship between The Transactional and Transformational Leadership Style with The Organizational Comm - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT This study aims to examine the relationship between the transactional and transformational leadership style with the organizational commitment. The subjects of this research were 202 female nurses. They were randomly selected from the population of two hospitals in Yogyakarta. The data were collected by the means of two questionnaires: the multifactor leadership questionnaire revealed transactional and transformational leadership, while the commitment questionnaire revealed organizational commitment. The data were analyzed by using multiple correlation and multiple partial correlation analysis. The result analysis shows that (1) the transactional and transformational leadership style was significantly correlated with the organizational commitment, (2) the transformational leadership style was significantly correlated with the organizational commitment, (3) the transactional leadership style was not significantly correlated with the organizational commitment, (4) the employment period was significantly correlated with the organizational commitment, (5) the age was not significantly correlated with the organizational commitment. The effective contribution of the transformational leadership style to organizational commitment was 15,818%